A technique to generate plausible counter-operation procedures for an emergency situation based on a model expressing functions of components. Issue 5 (4th May 2017) - Gofuku, Akio; Inoue, Takahisa; Sugihara, Taro
ABSTRACT: In large-scale engineering plants like nuclear power plants, various anomalies and accidents are usually predicted and efficient measures to minimize the damage from them have been implemented. However, when an unexpected anomaly or accident occurs, operators are asked to take flexible responsive actions to avoid its development to a catastrophic situation and to minimize the influence and damage by the accident. Considering the lessons learned from Fukushima Daiichi accidents, it is important to develop a system to support counter activities by operators and plant staff in an accidental plant condition that is not covered by emergency operating procedures prepared. The purpose of this study is to develop a technique for generating plausible operation procedures under such unexpected emergency situations. The multilevel flow modeling (MFM), a method to represent the functions of components and their relations, is applied as a framework to model functions of components. The technique uses some additional data and knowledge for deriving operation procedures. The applicability of the technique is confirmed by trial operation procedure generations for pressurized water reactor (PWR) loss-of-coolant accident cases with the conditions of some failures of safety systems.